1993
DOI: 10.1093/oxfordjournals.humrep.a138185
|View full text |Cite
|
Sign up to set email alerts
|

CLINICAL REPORT: The use of intravenous albumin in patients at high risk for severe ovarian hyperstimulation syndrome

Abstract: Previous experiences in subjects with other forms of third space fluid accumulation have shown that albumin is efficacious in preventing and correcting haemodynamic instability. Using a similar approach in an effort to increase the serum oncotic pressure and to reverse the leakage of fluids from the intravascular space, high risk subjects for severe ovarian hyperstimulation syndrome (SOHS) were treated with albumin. In a recent large study two high risk factors were identified, i.e. the number of oocytes and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0
8

Year Published

1995
1995
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(58 citation statements)
references
References 0 publications
0
49
0
8
Order By: Relevance
“…Nevertheless, a recent meta-analysis of five randomized controlled trials demonstrated that prophylactic albumin administration significantly reduced risk of developing OHSS. 43 Metformin an insulin sensitizer added to ovulation induction in women with PCOS undergoing IVF treatment with or without cabergoline has also been documented to reduce the risk of developing OHSS. Khattab et al in their work found a significant reduction in the incidence of this complication in the group taking metformin and concluded that Metformin is a safe, cheap drug that can help in prevention of OHSS.…”
Section: Other Preventive Measuresmentioning
confidence: 99%
“…Nevertheless, a recent meta-analysis of five randomized controlled trials demonstrated that prophylactic albumin administration significantly reduced risk of developing OHSS. 43 Metformin an insulin sensitizer added to ovulation induction in women with PCOS undergoing IVF treatment with or without cabergoline has also been documented to reduce the risk of developing OHSS. Khattab et al in their work found a significant reduction in the incidence of this complication in the group taking metformin and concluded that Metformin is a safe, cheap drug that can help in prevention of OHSS.…”
Section: Other Preventive Measuresmentioning
confidence: 99%
“…5,6,7 Early identification of the patients at risk and prevention of OHSS is clinically important. Several methods have been recommended for minimizing the probability of the syndrome in high risk pa tients including canceling the cycle before administration of hCG or reduction of the ovulatory hCG dose, 8 withhold ing luteal support with hCG, 9 cryopreservation of all em bryos for further use in a non-stimulated cycle, 10 repeated aspiration of ovarian follicles and early corpus luteum cysts, 11 administration of human albumin at the time of hCG injection, 12 use of GnRh analogue to trigger ovulation, 13 and vaginal aspiration of ascites. 14 Ketoconazole, a broad-spectrum imidazole antimycotic agent, was recently reported to reduce the incidence of OHSS in PCOS women undergoing superovulation program by gonadotropins.…”
Section: Introductionmentioning
confidence: 99%
“…Asch and colleagues first reported prophylactic administration of albumin prevented OHSS in 36 high risk patients (18). Shoham et al (10) described a similar benefit in a small random prospective study where 16 high risk OHSS patients received albumin and did not develop severe OHSS, whereas a control group (no albumin) had 4/15 develop severe OHSS.…”
Section: Discussionmentioning
confidence: 96%